Measuring the Impact of Agglomeration on Productivity: Evidence from Chilean Retailers. (June 2014) - Garate, Sergio; Pennington-Cross, Anthony
This research extends the agglomeration literature to a country that has not been studied and a market sector that has received little attention. The majority of research that examines how density affects productivity has indirectly measured productivity through worker wages or property prices. The research uses individual supermarkets' store productivity, proxied by 10 years of annual sales per square foot. Studying supermarkets permits the examination of the effect consumers might have on productivity. Agglomerations (density) could increase or decrease productivity depending on the relative extent of increased competition versus productivity gains, as consumers choose where to shop based on their interests in reducing shopping time (transport costs) and comparison shopping (product quality and pricing). Stores are described by who operates the store, the brand of the store and the size of the store. Results indicate that density has a differential impact depending on the store itself and the mix of stores nearby.